Palaeoepidemiology in extinct vertebrate populations: factors influencing skeletal health in Jurassic marine reptiles - Pardo Perez, Judith Mariana; Kear, Benjamin; Maxwell, Erin E. (My University, 2019)
Palaeoepidemiological studies related to palaeoecology are rare, but have the potential to provide information regarding ecosystem-level characteristics by measuring individual health. In order to assess factors underlying the prevalence of pathologies in large marine vertebrates, we surveyed ichthyosaurs (Mesozoic marine reptiles) from the Posidonienschiefer Formation (Early Jurassic: Toarcian) of southwestern Germany. This Formation provides a relatively large sample from a geologically and geographically restricted interval, making it ideal for generating baseline data for a palaeoepidemiological survey. We examined the influence of taxon, anatomical region, body size, ontogeny and environmental change, as represented by the early Toarcian Oceanic Anoxic Event, on the prevalence of pathologies, based on a priori ideas of factors influencing population skeletal health. Our results show that the incidence of pathologies is dependent on taxon, with the small-bodied genus Stenopterygius exhibiting fewer skeletal pathologies than other genera. Within Stenopterygius, we detected more pathologies in large adults than in smaller size classes. Stratigraphic horizon, a proxy for palaeoenvironmental change, did not influence the incidence of pathologies in Stenopterygius. The quantification of the occurrence of pathologies within taxa and across guilds is critical to constructing more detailed hypotheses regarding changes in the prevalence of skeletal injury and disease through Earth history.
Keywords: palaeopathology; palaeontology; ichthyosauria; palaeoecology; posidonienschiefer formation; marine reptiles